О методике изучения распределения животных - Владышевский, Д.В. (Вестник зоологии, 1968)
As shown on the example of birds, when studying animal distribution in nature by the method of trial grounds or another one similar to it, it is very difficult to obtain the comparable indices because the types of distribution are changed depending on the dimensions of grounds. When the grounds are small and an average occurence of ani-mals is equal to unit the calculated distribution is closer to the Poisson one, and when the average occurrence of animals is about some units — it is closer to the normal one. For obtaining the comparable objective values as an index of distribution type of animals it is recommended to use the distance between two next points of their occurence.